2010
DOI: 10.1371/journal.pone.0011457
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Causes Epigenetic Repression of hTERT Expression in Human Breast Cancer Cell Lines

Abstract: BackgroundSulforaphane (SFN), an isothiocyanate found in cruciferous vegetables, is a common dietary component that has histone deacetylase inhibition activity and exciting potential in cancer prevention. The mechanisms by which SFN imparts its chemopreventive properties are of considerable interest and little is known of its preventive potential for breast cancer.Principal FindingsWe found that SFN significantly inhibits the viability and proliferation of breast cancer cells in vitro while it has negligible e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
285
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(306 citation statements)
references
References 42 publications
16
285
3
2
Order By: Relevance
“…The effective concentration (EC 50 ) was found to be 25μM SFN for duration of 24h (Figure 1). Other studies also showed that SFN treatment significantly reduces cell viability of various cancer cells i.e., human leukemia T-cells, breast, pancreatic, lymphoblastoid and glioma cancer cells in a dose-dependent manner (Fimognari et al, 2002;Misiewicz et al, 2004;Meeran et al, 2010;Huang et al, 2012;Li et al, 2012). Interestingly, SFN has a safe cytotoxicity profile towards the normal cells thus it can be utilized in the development of safe cancer treatment strategies (Sharma et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The effective concentration (EC 50 ) was found to be 25μM SFN for duration of 24h (Figure 1). Other studies also showed that SFN treatment significantly reduces cell viability of various cancer cells i.e., human leukemia T-cells, breast, pancreatic, lymphoblastoid and glioma cancer cells in a dose-dependent manner (Fimognari et al, 2002;Misiewicz et al, 2004;Meeran et al, 2010;Huang et al, 2012;Li et al, 2012). Interestingly, SFN has a safe cytotoxicity profile towards the normal cells thus it can be utilized in the development of safe cancer treatment strategies (Sharma et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation and RT-PCR were performed as described previously (6,8,21,22). The primer sequences and annealing temperatures (T A ) are given in Supplementary Table S2.…”
Section: Rna Extraction and Quantitative Real-time Pcrmentioning
confidence: 99%
“…The procedures have been described previously (6,21). Briefly, equal amounts of protein were electrophoresced and transferred onto a 0.45-mm polyvinylidene difluoride (PVDF) membrane.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations